Pengaruh Pola Asuh Orangtua Terhadap Tingkah Laku Remaja Usia 15-17 Tahun di Desa Jumateguh Kecamatan Siempat Nempu Kabupaten Dairi Tahun 2022 - Ingrina Simaremare; Dame Taruli Simamora; Damaiyanti Nababan; Senida Harefa; Dorlan Naibaho (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study was to determine the positive and significant effect of Parenting on Adolescent Behavior in Jumateguh Village, Siempat Nempu Sub-District, Dairi Regency in 2022. The research method used is quantitative method with descriptive statistics. The population is all teenagers aged 15-17 years in Jumateguh Village Siempat Nempu Dairi Regency in 2022 as many as 313 students and a sample of 64 people was determined using random sampling technique. Data were collected using a positive closed questionnaire of 38 items, namely 16 items for variable X and 22 items for variable Y. The results of data analysis show that there is a Positive and Significant Influence Between Parental Parenting on the Behavior of Adolescents aged 15-17 years in Jumateguh Village, Siempat Nempu District, Dairi Regency in 2022: 1). Test analysis requirements: a) positive relationship test obtained rxy value = 0.488> rtable (a=0.05, n = 64) = 0.244. b) Significant relationship test obtained tcount = 4.400> ttable (a=0.05, dk = n-2 = 62) = 2.000. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂ = "26.98"+0.84X. b) Regression determination coefficient test (r2) = 23.8%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (a=0.05, dk numerator k = 20, dk denominator = n-2 = 64-2 = 62), namely 19.36> 1.39. Thus Ha is accepted and H0 is rejected.